IMPACTO DE LA CONFIANZA Y EL BIENESTAR SUBJECTIVO EN LA JUSTICIA PROCESAL: UN ESTUDIO DE MEDIACION - Jabeen, Irum; Ishaque1, Sadia; Khakwani, Maria; Luqman, Rabia; Irshad, Saadia (Revista Inclusiones, 2018)
The purpose of this paper is to examine the impact of trust and subjective well-being on the perceived procedural justice with the mediating effect of psychological contract. This study was conducted in the context of Pakistan. Data was collected through self-administered questionnaire. These were distributed to the teachers of universities studied. A total of 385 teachers were interviewed. The mediating variable, “psychological contract” was measured by transactional and relational contracts. All variables were measured using five-point Likert scale. Results show that, first, trust must be fostered for organizational relationships to be developed and nurtured. Second, subjective well-being plays a significant role towards the development of psychological contracts of employees. Third, Psychological contract doesn‟t mediate the relationship between trust, subjective well-being and procedural justice perception.